2005
DOI: 10.1186/1471-2466-5-2
|View full text |Cite
|
Sign up to set email alerts
|

The Darlington and Northallerton Long Term Asthma Study: pulmonary function

Abstract: Background: The Darlington and Northallerton Asthma Study is an observational cohort study started in 1983. At that time little was published about long term outcome in asthma and the contribution of change in reversible disease or airway remodelling to any excess deterioration in function. The study design included regular review of overall and fixed function lung. We report the trends over fifteen years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Other studies displayed the frequent coexistence of emphysema with LBW [9,10]. Independent of smoking influence on asthma, the FVC% levels observed in this study was also confirmed in previous studies [11,12].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies displayed the frequent coexistence of emphysema with LBW [9,10]. Independent of smoking influence on asthma, the FVC% levels observed in this study was also confirmed in previous studies [11,12].…”
Section: Discussionsupporting
confidence: 91%
“…This underlines that new onset asthma is as common in older adults as in young adults, although it is more frequently under recognized [2,18]. Hence, the reduction in lung function in older asthma patients could reflect long-standing, unrecognised and hence untreated, asthma [6,9]: This is supported by findings reported from the Tucson study, where 63% of older adults who developed asthma after the age of 60 years, reported asthma-like symptoms years before being diagnosed with asthma [1]. However, in a later report from the same study, a similar proportion among young adults reported wheezing or shortness of breath (69%), prior to a diagnosis of asthma [30].…”
Section: Discussionmentioning
confidence: 96%
“…Non-reversible airflow obstruction in older adults with incident asthma could relate to a pre-existing decrement, or to an accelerated decline in lung function [2,9,12]. However, there is limited evidence from representative, unselected populations, comparing lung function in older adults versus young adults with newly diagnosed asthma.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recommended variability cut-off 62,63,66 (within repeated sessions) is 150 ml for FEV 1 …”
Section: Fev 1 Decline Assessment and Some Functional Aspectsmentioning
confidence: 99%
“…Asthma is a chronic inflammatory airway disease characterized by an accelerated decline in lung function [1][2][3][4] . This chronic and persistent inflammation can cause a progressive sub-endothelial and sub-basement membrane thickening, smooth muscle hypertrophy, extracellular matrix deposition and altered vascular components that consequently determine the development of airway remodeling thus reducing bronchial caliber in time [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%